2014
DOI: 10.1016/j.envint.2014.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal serum concentrations of per- and polyfluoroalkyl substances and their predictors in years with reduced production and use

Abstract: Determining maternal concentrations of per- and polyfluoroalkyl substances (PFASs) and the relative impact of various demographic and dietary predictors is important for assessing fetal exposure and for developing proper lifestyle advisories for pregnant women. This study was conducted to investigate maternal PFAS concentrations and their predictors in years when the production and use of several PFASs declined, and to assess the relative importance of significant predictors. Blood from 391 pregnant women part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

31
104
3
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 60 publications
31
104
3
2
Order By: Relevance
“…On the other hand, maternal PFASs were comparable to another Norwegian study with a similar blood collection period (Berg et al, 2014). …”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, maternal PFASs were comparable to another Norwegian study with a similar blood collection period (Berg et al, 2014). …”
Section: Discussionsupporting
confidence: 71%
“…We estimated a crude average reduction of 44% in both PFOS and PFOA and 47% in PFHxS, while the adjusted changes, estimated with the predicted PFAS levels of the 2 nd pregnancy as derived from the multivariate models, were similar (PFOS= −45%, PFOA= −48%, PFHxS= −57%). A previous study in northern Norwegian pregnant women found similar effect estimates on PFAS levels in relation to having one previous pregnancy (PFOS= −30%, PFOA= −45%, PFHxS= −37%) (Berg et al, 2014). Within the MoBa study and similar to our results, Brantsaeter et al found 46% average reduction of PFOS concentrations for multiparous compared to nulliparous women, while for PFOA and PFHxS the estimates were very different from ours (70% and 19%, respectively) (Brantsaeter et al, 2013).…”
Section: Discussionsupporting
confidence: 55%
“…This holds particularly true in the light of some recent toxicological findings (Grandjean and Budtz-Jørgensen, 2013) that showed that immunotoxicity in children might be associated with below average serum concentrations of PFOS and PFOA in women who were of reproductive age in recent population studies (Brede et al, 2010;Kärrman et al, 2013;Axmon et al, 2014;Berg et al, 2014) and below the median concentration values assessed in the present study.…”
Section: Discussionmentioning
confidence: 49%
“…41 When comparing the exposure in high fish consumers and metal plating workers with the background control group it should be noted that serum concentrations were not adjusted for demographic factors such as age/birth cohort and gender which are known to be important predictors of human serum concentrations for other PFASs. 42,43 More comprehensive biomonitoring studies from different regions of China are, therefore, needed to better understand the human exposure to PFESAs.…”
mentioning
confidence: 99%